High-performance capacitive deionization using nitrogen and phosphorus-doped three-dimensional graphene with tunable pore size. (10th March 2020) - Han, Deng-Cheng; Zhang, Chun-Miao; Guan, Jing; Gai, Li-Hong; Yue, Reng-Yu; Liu, Lin-Na; Afzal, Muhammad Zaheer; Song, Chao; Wang, Shu-Guang; Sun, Xue-Fei
Abstract: Capacitive deionization (CDI) is considered as a potential water purification technology for electrochemical removal of the salt from aqueous solutions. However, the development of an electrode material with adequate electro adsorption rate and capacity is still a major challenge. In this study, a N and P-doped three-dimensional (3D) structure of graphene with high conductivity and capacitance for high performance CDI was synthesized and possessed tunable pore size through phosphoric acid activation. It had a large specific surface area of 567.14 m 2 g −1 due to the 3D hierarchical porous structure and highly crosslinked networks of graphene sheets. This novel material also had a high specific capacitance (177.19 F g −1 ). High specific capacitance and interaction of micropores with mesopores improved the desalination capacity up to 20.93 mg g −1 . Consequently, the materials with high specific surface area, better specific capacitance and tunable pore size can have a great potential for efficient and practical desalination applications. Graphical abstract: Image 1 Highlights: High performance capacitive deionization with N-doped three-dimensional graphene electrode was achieved. The electrode materials have high specific area, specific capacitance, and hierarchical pores structures. Capacitive deionization performance possessed electrosorption capacity of 20.93 mg g −1 and maximum capacity of 30.92 mg g −1 .